The pandemic of COVID-19 decreased adherence to treatment among hypertension patients at Dr. Zainoel Abidin Hospital - Ghina Salsabila Rahman; Muhammad Ridwan; Hilwah Nora; Maimun Syukri; Fitri Dewi Ismida (Trends in Infection and Global Health, 2021)
Hypertension is one of the leading causes of mortality and morbidity worldwide. Treatment adherence is an essential factor in controlling blood pressure among hypertensive patients. This study aimed to evaluate the effect of the Coronavirus disease 2019 (COVID-19) pandemic on treatment adherence among hypertensive patients at Dr. Zainoel Abidin Hospital, Aceh, Indonesia, as well as to determine its associated factors. A cross-sectional study was conducted at the Cardiac Center by utilizing medical records of hypertensive patients visiting during the period of April-July 2019 and December 2020-March 2021. Bivariate analysis using the Kruskal-Wallis test was employed to examine the effect of the COVID-19 pandemic on patients’ adherence. The results showed that the number of patients adhering to treatment significantly decreased (p=0.000) by 22.7%, from 179 patients in 2019 to 64 patients in 2020. The data also suggested a significant positive association between residential and patient adherence before the pandemic (p=0.006); however, no significant difference was observed between residential and patients’ adherence after the pandemic (p=0.282). Furthermore, our study found no association between age and adherence before and after the pandemic (p=0.690 in 2019 and p=0.125 in 2020). In conclusion, the pandemic of COVID-19 significantly affected treatment adherence among patients with hypertension at Aceh provincial hospital, with a decreased number in patient visits up to 22.7%.